2013
DOI: 10.1111/brv.12051
|View full text |Cite
|
Sign up to set email alerts
|

The application of species criteria in avian taxonomy and its implications for the debate over species concepts

Abstract: The debate over species concepts has produced a huge body of literature on how species can, may or should be delimited. By contrast, very few studies have documented how species taxa are delimited in practice. The aims of the present study were to (i) quantify the use of species criteria in taxonomy, (ii) discuss its implications for the debate over species concepts and (iii) assess recent claims about the impact of different species concepts on taxonomic stability and the 'nature' of species. The application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 94 publications
(106 reference statements)
2
80
0
1
Order By: Relevance
“…Out of 33032 valid fish species recognized in FishBase (Froese & Pauly, 2015), only 59 species include 2-6 subspecies, many of them obsolete. The use of subspecies is contentious in taxonomy as a whole and has been contested as being inconsistently applied and/or incongruent with genetic variation and/or lacking evolutionary context (e.g., Gippoliti & Amori, 2007;Kodandaramaiah et al, 2012;Kullander, 1999;Sangster, 2014;Wilson & Brown, 1953;Zink, 2004). The case of P. cupanus is further testimony to the confusing nature of trinomina.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 33032 valid fish species recognized in FishBase (Froese & Pauly, 2015), only 59 species include 2-6 subspecies, many of them obsolete. The use of subspecies is contentious in taxonomy as a whole and has been contested as being inconsistently applied and/or incongruent with genetic variation and/or lacking evolutionary context (e.g., Gippoliti & Amori, 2007;Kodandaramaiah et al, 2012;Kullander, 1999;Sangster, 2014;Wilson & Brown, 1953;Zink, 2004). The case of P. cupanus is further testimony to the confusing nature of trinomina.…”
Section: Discussionmentioning
confidence: 99%
“…Weakley's (2015) classification recognizes seven species-level concepts -more than any other taxonomy. The taxonomic history is evidently complex, but no more complicated than that of many other continuously revised groups [1,20,32,35,43,68,77,90]. The poor performance of names as identifiers of divergent taxonomic meanings is not exceptional for the field (herein broadly defined to include phylogenetics).…”
Section: Building Better Identifiers For Biodiversity Datamentioning
confidence: 99%
“…Such cases are frequent in taxonomy, and they cannot be reduced to the differences in degree of resolution [26,65,68,77]. As an example, the 1950/1948 classifications of the Andro-UC concur that there are three identically named species-level concepts entailed in the complex (Fig.…”
Section: Building Better Identifiers For Biodiversity Datamentioning
confidence: 99%
“…The increase results from more taxonomic splits than lumps, while new species discoveries are rather few. A recent review of taxonomic revisions concluded that taxonomy has improved as a scientific discipline with a more integrative conceptual framework and better empirical evidence underlying species delimitation (Sangster 2014). Despite the debate over species concepts, where proponents of the phylogenetic species concept have been accused of causing taxonomic inflation (Isaac et al 2004), there is a growing consensus that species are cohesive lineages with a distinct evolutionary history and intrinsic barriers to gene flow across their borders.…”
mentioning
confidence: 99%